Analisis Pemanfaatan Dana Transfer untuk Kemandirian Pembiayaan Daerah di Indonesia Menggunakan Model Struktural Partial Least Square - Algifari, Algifari; Nurkhin, Ahmad; Saputro, Iwan Hardi (Business and Accounting Education Journal, 2021)
The aims of this study is to examine the effect of General Allocation Funds (DAU) and Special Allocation Funds (DAK) on Original Local Government Revenues (PAD) in Indonesia using APBD data for 33 provinces in Indonesia for 2016-2018. The research hypothesis was tested using the Partial Leas Square structural equation model. The results showed that DAU had a negative effect on PAD, while DAK had a positive effect on PAD. Capital Expenditures (BM) were able to mediate DAU's effects on PAD. Based on the results of this study, the researchers recommend that the DAU received by the local government from the central government should be used to increase Capital Expenditures (BM) in order to increase PAD.